The Influence of the School Environment on the Formation of Children's Character - Abdul Azis; Sukma Utami; Lyn Cronin; Ahmad H. Al Sanie (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study investigates the influence of the school environment on the formation of children’s character within the context of Civics subjects at South Galesong District, Takalar Regency. By employing a descriptive qualitative research design, the study examines the interplay of various factors educators, students, canteens, classrooms, and playing fields in shaping character development. Two informants, selected for their knowledge and insights, contribute valuable perspectives to the research. Methodology: The research design is descriptive and qualitative. The sample comprises class V students, and the study involves two informants who possess relevant knowledge regarding the influence of the school environment on character formation. Data collection methods include observation, documentation, and in-depth interviews. Qualitative analysis is applied to the collected data. Main Findings: The study reveals nuanced insights into the Influence of the School Environment on the Formation of Children’s Character. Interviews with informants highlight both positive and negative influences. Educators play a crucial role, impacting character development through their teaching methods and interactions. Similarly, students’ behavior and peer dynamics significantly contribute to character formation. Surprisingly, even seemingly mundane aspects such as canteens and playing fields influence children’s values and attitudes. Novelty/Originality of this study: This research contributes novel insights by emphasizing the pivotal role of the school environment in character formation. By providing practical recommendations, it aims to empower elementary school 77 Kanaeng and other educational institutions to cultivate resilient, compassionate, and morally grounded individuals—the bedrock of a thriving Indonesian society.